1998
DOI: 10.1248/cpb.46.1008
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Foodstuffs. XIV. On the Bioactive Constituents of Moroheiya. (2): New Fatty Acids, Corchorifatty Acids A, B, C, D, E, and F, from the Leaves of Corchorus olitorius L. (Tiliaceae): Structures and Inhibitory Effect on NO Production in Mouse Peritoneal Macrophages.

Abstract: Following the characterization of the glycosidic constituents in a medical foodstuff "moroheiya," the leaves of Corchorus olitorius L., four higher fatty acids with a trienone function, corchorifatty acids, A, B, C, and D, an undecanoic acid, corchorifatty acid E, and a trihydroxyfatty acid, corchorifatty acid F, were isolated from the less polar fraction of "moroheiya". The structures and optical purity of corchorifatty acids were determined on the basis of chemical and physicochemical evidence. Corchorifatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…27 3,6,8,9), two methines (H-5, 7), and three quaternary carbons (C-4, 10, 11). As shown in Figure 3, the 1 H-1 H COSY experiment indicated the presence of two partial structures (C-1-3 and C-5-9), and in the HMBC experiment, long-range correlations were observed between the following proton and carbon pairs (H-5 and C-4; H 2 -12 and C-7, 13; H 3 -13 and C-7, 11, 12; H 3 -14 and C-1, 5, 9, 10; H 3 -15 and C-3-5).…”
Section: Resultsmentioning
confidence: 99%
“…27 3,6,8,9), two methines (H-5, 7), and three quaternary carbons (C-4, 10, 11). As shown in Figure 3, the 1 H-1 H COSY experiment indicated the presence of two partial structures (C-1-3 and C-5-9), and in the HMBC experiment, long-range correlations were observed between the following proton and carbon pairs (H-5 and C-4; H 2 -12 and C-7, 13; H 3 -13 and C-7, 11, 12; H 3 -14 and C-1, 5, 9, 10; H 3 -15 and C-3-5).…”
Section: Resultsmentioning
confidence: 99%
“…In the family of NOS, inducible NOS (iNOS) is specifically involved in pathologic aspects with the overproduction of NO and can be expressed in response to proinflammatory agents such as interleukin-1b, tumor necrosis factor-a, and LPS in various cell types including macrophages. As a part of our studies to characterize the bioactive components of natural medicines, we have investigated various NO production inhibitors, i.e., higher unsaturated fatty acids, 27) polyacetylenes, [28][29][30] coumarins, 28,30,31) flavonoids, 29,32) stilbenes, 33,34) lignans, [35][36][37] sesquiterpenes, [38][39][40][41][42][43][44][45] diterpenes, 46,47) triterpenes, [48][49][50][51] diarylheptanoids, [52][53][54] cyclic peptides, 50) alkaloids, 55,56) and phenylpropanoids. 5,6,37) Continuing of these studies, the effects of the principal constituents from E. expansa on NO production from LPS-activated macrophages were examined, and the results were summarized in Table 2.…”
Section: Inhibitory Effects On No Production In Lps-activated Mouse Pmentioning
confidence: 99%
“…In the family of NOS, inducible NOS is specifically involved in the pathologic aspects with overproduction of NO and can be expressed in response to proinflammatory agents such as interleukin-1b, tumor necrosis factor-a, and LPS in various cell types including macrophages, endothelial cells, and smooth muscle cells. As a part of our studies to characterize the bioactive components of natural medicines, we reported various NO production inhibitors, i.e., higher unsaturated fatty acids, 28) poly-acetylenes, 2,29) coumarins, 2) flavonoids, 29,30) stilbenes, 31,32) lignans, 33,34) sesquiterpenes, [35][36][37][38][39][40][41] diterpenes, 42,43) triterpenes, [44][45][46][47] diarylheptanoids, 48,49) cyclic peptides, 46) and alkaloids. 50,51) As a continuation of these studies, the effects of the coumarin constituents from the flowers and leaves of A. furcijuga on NO production from LPS-activated macrophages were examined, and the results are summarized in Table 2.…”
Section: Inhibitory Effects On No Production In Lps-activated Mouse Pmentioning
confidence: 99%